2001
DOI: 10.1081/ddc-100105173
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Content of the Constituents ofHypericum perforatumL. and Some Commercial Extracts

Abstract: Seven samples of Hypericum perforatum L. (St. John's wort) were collected throughout Tuscany; the dried extracts were assayed to determine the concentration of the constituents. Total flavonol content ranged from 4.58% to 15.90%; hypericins ranged from 0.05% to 0.11%; and hyperforins ranged from 1.37% to 20.80%. In addition, four commercially dried extracts were analyzed using the same high-performance liquid chromatographic (HPLC) method; their flavonol contents varied from 10.64% to 15.01%, hypericins varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 6 publications
2
39
1
Order By: Relevance
“…Kukric et al (2013) evaluated the antioxidative effect of dried ethanolic extract of E. arvense, which had an IC50 and AAI (antioxidant activity index) of 13.5 and 3.9, respectively. Although present findings are somehow similar to results of those earlier studies, differences in extraction and activity methods, climate, soil, environmental factors, diseases, and pesticide treatments, harvest time, drying and storage methods and plant parts used in analyses may significantly affect the antioxidant activity of plants (Bergonzi et al, 2001;Wang and Zheng, 2001). In previous scientific studies, all over the world on nutritive composition of wild plants high quantities of minerals, especially K, Na, Ca, P, Mg (Guil Guerrero et al, 1998;Agrahar-Murugkar and Subbulakshmi, 2005) are indicated.…”
Section: Discussioncontrasting
confidence: 32%
“…Kukric et al (2013) evaluated the antioxidative effect of dried ethanolic extract of E. arvense, which had an IC50 and AAI (antioxidant activity index) of 13.5 and 3.9, respectively. Although present findings are somehow similar to results of those earlier studies, differences in extraction and activity methods, climate, soil, environmental factors, diseases, and pesticide treatments, harvest time, drying and storage methods and plant parts used in analyses may significantly affect the antioxidant activity of plants (Bergonzi et al, 2001;Wang and Zheng, 2001). In previous scientific studies, all over the world on nutritive composition of wild plants high quantities of minerals, especially K, Na, Ca, P, Mg (Guil Guerrero et al, 1998;Agrahar-Murugkar and Subbulakshmi, 2005) are indicated.…”
Section: Discussioncontrasting
confidence: 32%
“…Recently, H. perforatum naphthodianthrones have also been studied for their possible application in the photodynamic therapy of cancer [8]. The concentration of these constituents in the plant is particularly low, as mentioned above, varying from 0.01 to 0.03% and even in alcoholic or hydroalcoholic extracts it may reach up to 0.1 -0.4% [9]. Investigations in order to find other Hypericum sp.…”
Section: Introductionmentioning
confidence: 99%
“…The HPLC system consisted of a HP 1100 L instrument with a diode array detector managed by a HP 9000 (Bergonzi et al, 2001). Before the HPLC analysis, each sample was filtered through a cartridge-type sample filtration unit with a polytetrafluoroethylene (PTFE) membrane (d = 13 mm, porosity 0.45 μm, Lida manufacturing Corp.) and immediately injected.…”
Section: Hplc-dad and Hplc-ms Drug Analysesmentioning
confidence: 99%
“…To evaluate the constituents' content, an HPLC analysis was performed using a method described in the literature (Bergonzi et al, 2001). Identification of the constituents was performed using combined HPLC-diode array detection (DAD) analysis and HPLC-thermospray mass spectrometry.…”
Section: Hplc-dad and Hplc-ms Drug Analysesmentioning
confidence: 99%